Pengaruh Social Media Marketing, E-Service Quality, dan Review Content terhadap Minat Beli pada UMKM Produk Organik - Bagus Satriyo; Yeni Indriana; Musalim Ridlo (UNESA In Collaboration With APSMBI (Aliansi Program Studi dan Bisnis Indonesia), 2021)
Advances in information technology and digital-based economy expand the potential for entrepreneurship. Market segmentation becomes more extensive due to an online marketplace to sell goods and services. Online marketplace company needs an edge to compete with other similar businesses. Nyayur uses various marketing strategies to be able to compete. This study aimed to determine the influence of social media marketing, review content, and e-service quality on buying interest among users of Nyayur in Salatiga. The data is collected using purposive sampling techniques with questionnaires distributed directly to fifty users of Nyayur. The data obtained were processed using IBM SPSS statistics 25. The results showed that social media marketing, e-service quality, and content review do not influence purchase intention. This research can be an additional consideration for Nyayur.com in improving the quality of its operations, where this research provides factual evidence from consumers regarding their perception of Nyayur.com. So that this research can be used as material for monitoring and evaluation (Monev) of e-commerce platforms to improve the quality and professionalism of work, especially for Nyayur. com. Services using social media promotions can update their marketing strategy, considering that most users are housewives who do not actively use social media in the form of platforms. E-service quality can provide product consulting services for fruit and vegetables via calls or Whatsapp. Reviewing content on nyanyur.com is essential to support the progress of its performance. Consumers who provide the best reviews can be rewarded to help the nyayur.com application in the future.